Meta-analysis: Fiscal multiplier - Michal Hlaváček; Ilgar Ismayilov (Charles University in Prague, Institute of Economic Studies (IES), 2022)
Interest in fiscal policy has been dynamically improved in the last two decades; the number of research conducted on this topic has significantly increased in recent years. One of the key areas in fiscal policy investigations is the size of the fiscal multiplier, and most studies find contradictory results. In the current study, the unique dataset of 132 studies and more than 3200 observations were used to conduct a meta-analysis on multiplier effects, and several linear and non-linear models were involved in implementing this exercise. Additionally, Bayesian Model Averaging was first implemented to investigate heterogeneity effects in the meta-analysis of the fiscal multiplier. The results show that the fiscal multiplier is significantly less than one in the range of 0.75- 0.82. Moreover, the main contribution of the current study to the fiscal policy literature is disentangling the existence of selection publication bias in the literature.
Keywords: E62; 330; fiscal multiplier; meta-analysis; publication bias